Loss of apical suction assessed by noninvasive pressure differences and twist in acute heart failure: a novel method using vector flow mapping. (14th October 2021) - Ido, S; Masuda, K; Yoshimura, S; Tanaka, H; Stugaard, M
Abstract: Background: Early diastolic intraventricular pressure difference (IVPD) reflects left ventricular (LV) apical suction, and IVPD is closely related to cardiac function, especially LV twist. Vector Flow Mapping (VFM) allows visualization of regional pressure distribution and noninvasive quantification of IVPD. The purpose of the present study was to investigate if and how IVPDs are related to LV twist in a model of acute heart failure (HF). Methods: In 15 open-chest dogs, HF was induced by intracoronary injection of microspheres. The HF model was classified into two groups based on the LV end-diastolic pressure (LVEDP) (group1: LVEDP<18 mmHg (n=10), group2: LVEDP≥18 mmHg (n=8)). Color Doppler images from apical long-axis views were acquired at baseline and during HF. From these images, pressure differences (ΔP) were calculated along the LV inflow tract throughout the cardiac cycle. For the purpose of this study, the differences between apex and base during isovolumic relaxation time (ΔPIRT) and rapid early inflow period (ΔPE) were used for analyses. Furthermore, apical and basal short axis high frame rate 2D images were acquired, and peak rotation and peak twist were analyzed. Results: LVEDP was 7±9, 14±2, 21±3 mmHg for baseline, group1 HF, and group2 HF, respectively. Pressure differences (both ΔPIRT and ΔPE) were visibly changed by the increase of LVEDP (Figure), and the magnitude of ΔPIRT, ΔPE and peak twist decreased significantly with the severity of heart failure. There were significant relationships between pressure differences (ΔPIRT and ΔPE) and dP/dtmin, tau, EF and peak twist (Table). In multivariate analyses, tau and peak twist were independent predictors for ΔPIRT and peak twist was independent predictor for ΔPE. Conclusion: VFM analysis is feasible to noninvasively assess the IVPDs in acute heart failure. The IVPDs are closely related to the twisting motion of the LV, and reflect loss of apical suction during severe HF. Funding Acknowledgement: Type of funding sources: None.